Efficacy of entomogenous fungi on biological suppression of Pentalonia nigronervosa f. caladii Van der Goot of cardamom (Elettaria cardamomum Maton) - VENUGOPAL, M J MATHEW, K A SAJU, M N (Journal of Spices and Aromatic Crops, 1998)
Experiments were conducted in the laboratory on the biological suppression of the aphid Pentalonia nigronervosa f. caladii of cardamom (Elettaria cardamomum) using four entomogenous fungi namely, Beauveria bassiana, B. brongniartii, Verticillium chlamydosporium and Metarhizium anisopliae. Fungal spore suspensions (1 x 107 spores/ml) when applied on the aphid colonies caused mortality to both apterous adults and nymphs ranging from 37.0 to 96.6 per cent and 32.S to 75.4 per cent, respectively. B. bassiana was the most potent biocontrol agent effecting 96.6 and 75.4 per cent mortality for adults and nymphs, respectively, in the indirect expsoure method and 65.9 and 70.9 per cent, respectively, in the direct exposure method.